The Philippine Teachers Concerns on Educational Reform Using Concern Based Adoption Model - Magallanes, Krizia; Chung, Jae Young; Lee, Sunbok (Frontiers in Education, 2022)
This study aims to identify the Philippines teachers’ concerns in the K-12 implementation. The Concerns Based Adoption Model was applied to determine the level of concerns, and the Stages of Concern Questionnaire has been administered to 400 teachers. Findings indicate that consequence and collaboration was the teachers’ current concern (impact stage). Furthermore, experience and education factors showed the biggest significance affecting their collaboration among teachers. These current concerns match the existing problems of Philippine education: poor PISA results and lack of resources. This research urges the Philippine government to promote professional development activities that encourage teamwork and collaboration among teachers.